PARIWISATA BERKELANJUTAN UNTUK PENINGKATAN DAYA SAING KAMPUNG BATIK GIRILOYO - Tioputri, Fenny Cintya; Sulistyo, Agung; Hayatri, Maria Ana Sila (Pusat Perencanaan dan Pengembangan Kepariwisataan, 2025)
This study aims to analyze the application of sustainable tourism in increasing competitive advantage in Kampung Batik Giriloyo Yogyakarta. This study uses a qualitative method with data collection techniques through interviews and other activities. The informants in this study were managers, the community and visiting tourists. Data were analyzed using the Miles and Huberman method. The study results show that Kampung Batik Giriloyo has comprehensively implemented the concept of sustainable tourism in three indicators: economy, socio-cultural, and environment. This condition can increase competitiveness as a culture-based tourist destination. Sustainable management makes Kampung Batik Giriloyo continue to exist as a centre for hand-drawn batik that can provide an impact and compete with other tourist attractions.